Low-temperature large-scale modeling of air flow stability in an inclined mine working with a heat source - Shalimov , A.V.; Zhikharev, S.Ya.; Semin, M.A.; Kuzminykh, E.G. (Perm Federal Research Centre Journal, 2026)
An analysis was carried out on the possibilities of large-scale modeling of downward airflow in inclined mine workings with a heat source within the parametric range of airflow instability. It was established that accurately reproducing model similarity to reality in this range is only possible within the framework of the Froude scaling rules with identical air temperature, which at the fire source reaches 1500 K or more. Since achieving such air heating under laboratory conditions is problematic, an attempt was made to obtain approximate low-temperature scaling relations based on estimated calculations targeting a threefold reduction in temperature with a tenfold reduction in geometric dimensions. The obtained relations were verified through numerical modeling of the thermal plug effect in the SolidWorks software suite, as well as on a laboratory simulation stand. The relative error in determining the overturning point of airflow due to thermal depression in model and full scale was 2%. Both methods of modeling the thermal plug effect showed the same dynamic scenario of airflow direction change via instability, in which the flow overturns gradually, forming large-scale convective vortices and multidirectional vertical velocity stratification across the cross-section.